Entre a vida e a obra: música e religião em Max Weber - Costa, Joicy Suely Galvão da (2013)
This study aims to analyze the relationship between music and religion in Max Weber s life and work, in a perspective that combines its intellectual productions in Sociology, in religion and art subfields. We developed a research in order to revisit the concept of rationalization, present in Weberian thought, and also to discuss how music and religion, as distinct spheres of life, star conflicts and alliances and build particular attitudes of action in the world, having the appearance of a rationality based on calculation in a central position to understand the construction of musical technique in the West and the autonomy of aesthetic enjoyment from religious enjoyment, previously linked. Regarding the procedure analysis, we built a symbolic cartography, according to Santos (2000), from selected works of Max Weber, as Religious rejections in the world and their directions (1982), among others. With the activity, we identified similarities and differences between music and religion in the author thoughts. We consider that the studied dimensions are important in Weberian analysis of the constitution of modern society and its cultural system, showing two distinct approaches to the issue of rationalization in the West